Preparation method and application of composite hollow fiber absorbing material
By coating the tricobalt tetroxide composite hollow fiber material in silica, the problems of poor impedance matching and easy oxidation in electromagnetic wave absorption in traditional magnetic nanomaterials are solved, and the wave absorption performance is improved and the preparation simplicity is achieved, and the electromagnetic wave absorption effect is excellent.
Patent Information
- Application Number
- CN202111583655.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-22
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-12-22
AI Technical Summary
Traditional magnetic nanomaterials have problems with poor impedance matching characteristics, easy oxidation and high density in electromagnetic wave absorption, making it difficult to achieve the requirements of thin absorption thickness, light weight, wide effective absorption frequency band and high absorption strength.
Silicon dioxide is used to coat tricobalt tetroxide composite hollow fiber material, and tricobalt tetroxide hollow fiber is prepared by electrospinning and calcining, and a silica cladding layer is formed on its surface to optimize the impedance matching and magnetic loss capability of the material.
It realizes electromagnetic wave absorption with strong wave absorption performance under thin thickness, simplifies the preparation process, has uniform material diameter and stable shell thickness, and has a wide range of electromagnetic wave absorption application value.
Smart Images

Figure CN114447621B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electromagnetic wave absorbing materials, and relates to a composite hollow fiber absorbing material and a preparation method and application thereof, and specifically relates to a silicon dioxide-coated cobalt tetroxide composite hollow fiber absorbing material and a preparation method thereof, as well as an application thereof in electromagnetic wave absorption. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] Electromagnetic wave absorbing materials have become an important means of achieving electromagnetic protection due to their wide range of applications. Traditional magnetic nanomaterials have high saturation magnetization and magnetic permeability, and high magnetic loss capacity, but they are easily oxidized and have poor impedance matching characteristics, which is not conducive to the effective absorption of electromagnetic waves; on the other hand, the high density and easy oxidation characteristics further limit the requirements of absorbing materials for "thin absorbing thickness, light weight, wide effective absorption frequency band, and high absorption intensity". Summary of the invention
[0004] The purpose of the present invention is to provide a composite hollow fiber absorbing material and its preparation method and application, so as to make the material have both strong loss and good impedance matching, and to use it for electromagnetic wave absorption, so that it has good impedance matching and strong loss capacity, and has strong absorbing performance at a thin thickness.
[0005] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0006] In a first aspect, the present invention provides a composite hollow fiber absorbing material, comprising a cobalt tetroxide hollow fiber and a silicon dioxide coating layer coated on the outside thereof.
[0007] In a second aspect, the present invention provides a method for preparing the composite hollow fiber absorbing material, comprising the following steps:
[0008] Electrospinning a precursor solution of cobalt salt to obtain fibers;
[0009] calcining the fiber to obtain cobalt tetroxide hollow fiber;
[0010] The cobalt tetroxide hollow fiber is dispersed in a silicon source solution, and the silicon source is hydrolyzed to obtain silicon dioxide, thereby obtaining a silicon dioxide-coated cobalt tetroxide composite hollow fiber absorbing material.
[0011] In a third aspect, the present invention provides the application of the composite hollow fiber absorbing material in the direction of electromagnetic wave absorption;
[0012] Furthermore, the composite hollow fiber absorbing material is used in the preparation of electromagnetic wave absorbing devices.
[0013] In a fourth aspect, the present invention provides an electromagnetic wave absorbing device, which is prepared from the composite hollow fiber absorbing material.
[0014] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0015] (1) The silica-coated cobalt tetroxide composite hollow fiber prepared by the present invention, on the one hand, silica is a low-loss dielectric material, which can optimize the impedance matching of the material, allowing electromagnetic waves to smoothly enter the interior of the material without reflection; on the other hand, since cobalt tetroxide is a weak magnetic material, it has a certain magnetic loss to the incident electromagnetic wave; thirdly, the presence of the hollow structure can not only optimize the impedance matching of the material, but also cause multiple scattering of the electromagnetic wave, thereby enhancing the material's loss of the electromagnetic wave.
[0016] (2) Compared with the prior art, the synthesis method of the present invention is simple, and only one electrospinning, one calcination and one coating are required to obtain the final product. The prepared silica-coated cobalt oxide composite hollow fiber material has a uniform diameter and a stable shell thickness, and no other by-products are generated during the whole process.
[0017] (3) The material prepared by the present invention has good wave absorbing effect, and therefore is expected to be widely used in the preparation of electromagnetic wave absorbing materials.
[0018] (4) The silica-coated cobalt oxide composite hollow fiber is compounded with a binder (paraffin) to obtain an absorbing material. The reflection loss of electromagnetic waves at a frequency of 7.65 GHz reaches -29.1 dB, and the matching thickness is only 4.27 mm. The silica-coated cobalt oxide composite hollow fiber material has high absorbing performance and has a wide range of application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0020] Figure 1 The figure is an XRD diagram of a silica-coated cobalt oxide composite hollow fiber prepared according to one or more embodiments of the present invention.
[0021] Figure 2 Figure a is a SEM image of the ferrosoferric oxide hollow fiber prepared in step (1) of Example 1, and Figure b is a SEM image of the silica-coated cobalt oxide composite hollow fiber finally obtained in Example 1.
[0022] Figure 3, which is a TEM image of the silica-coated cobalt oxide composite hollow fiber obtained in Example 1.
[0023] Figure 4 Figure a is the real part of the dielectric constant of the silica-coated cobalt oxide composite hollow fiber prepared in Example 1, Figure b is the imaginary part of the dielectric constant, and Figure c is the dielectric loss tangent.
[0024] Figure 5 Figure a is the real part of the magnetic permeability of the silica-coated cobalt oxide composite hollow fiber prepared in Example 1, Figure b is the imaginary part of the magnetic permeability, and Figure c is the magnetic loss tangent.
[0025] Figure 6 This is the reflection loss diagram of the silica-coated cobalt tetroxide composite hollow fiber absorber prepared in Example 1.
[0026] Figure 7 This is the reflection loss diagram of the solid prepared in Example 2.
[0027] Figure 8 This is the reflection loss diagram of the solid prepared in Comparative Example 1.
[0028] Fig. 9 This is the reflection loss diagram of the solid prepared in Comparative Example 2. DETAILED DESCRIPTION
[0029] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0030] In a first aspect, the present invention provides a composite hollow fiber absorbing material, comprising a cobalt tetroxide hollow fiber and a silicon dioxide coating layer coated on the outside thereof.
[0031] In some embodiments, the outer diameter of the cobalt trioxide hollow fiber is 60-90 nm, and the inner diameter is 20-40 nm.
[0032] In some embodiments, the thickness of the silicon dioxide coating layer is 10-20 nm.
[0033] In a second aspect, the present invention provides a method for preparing the composite hollow fiber absorbing material, comprising the following steps:
[0034] Electrospinning a precursor solution of cobalt salt to obtain fibers;
[0035] calcining the fiber to obtain cobalt tetroxide hollow fiber;
[0036] The cobalt tetroxide hollow fiber is dispersed in a silicon source solution, and the silicon source is hydrolyzed to obtain silicon dioxide, thereby obtaining a silicon dioxide-coated cobalt tetroxide composite hollow fiber absorbing material.
[0037] In some embodiments, the precursor solution of the cobalt salt is a mixed solution of the cobalt salt and a surfactant.
[0038] Furthermore, the cobalt salt is cobalt acetylacetonate or cobalt nitrate hexahydrate.
[0039] Furthermore, the surfactant is polyvinyl pyrrolidone or polyacrylonitrile.
[0040] Furthermore, the solvent of the cobalt salt precursor solution is N,N-dimethylformamide.
[0041] Furthermore, the concentration of the cobalt salt is 0.005-0.2 g / mL, and the concentration of the surfactant is 0.05-0.4 g / mL.
[0042] Furthermore, the concentration of the cobalt salt is 0.06-0.12 g / mL, and the concentration of the surfactant is 0.05-0.1 g / mL.
[0043] In some embodiments, the temperature of electrospinning is 20-40°C and the voltage is 10-15V;
[0044] Furthermore, the temperature of electrospinning is 30-40°C and the voltage is 10-12V;
[0045] Preferably, the temperature of electrospinning is 40°C and the voltage is 12V.
[0046] In this process, the polymer fluid formed by the solvent and the surfactant carries the polymer molecules for electrostatic spinning, and finally solidifies into fibers through the coagulation liquid. The above addition ratio, temperature and voltage range are conducive to the formation of the cobalt-containing hollow fiber precursor.
[0047] In some embodiments, the calcination temperature is 400-800° C., the heating rate is 1-5° C. / m / n, and the reaction time is 0.5-8 h.
[0048] Furthermore, the calcination temperature is 400-600°C, the heating rate is 1-3°C / m / n, and the reaction time is 1-4h.
[0049] Cobalt ions and polymers produce smooth-surfaced polyvinyl pyrrolidone-based precursor nanofibers. In the air atmosphere, the self-assembly of metals caused by the Kendall effect causes the metal oxide to grow toward the outer shell layer, eventually forming a hollow structure. The cobalt oxide hollow fiber reacts with the solution. Under the alkaline conditions provided by ammonia water, water and ethanol play the role of promoting hydrolysis and buffering, respectively, and finally form a silicon dioxide-coated cobalt oxide composite hollow fiber.
[0050] Furthermore, the calcination atmosphere is air.
[0051] In some embodiments, the silicon source solution is a mixed solution of ethanol, water, ammonia water and tetraethyl orthosilicate.
[0052] Furthermore, in the silicon source solution, the volume ratio of ethanol, water, ammonia water and tetraethyl orthosilicate is 30-50:5-15:0.2-1:0.1-1.
[0053] Furthermore, in the silicon source solution, the volume ratio of ethanol, water, ammonia water and tetraethyl orthosilicate is 30-40:5-10:0.3-0.8:0.1-0.5.
[0054] Preferably, in the silicon source solution, the volume ratio of ethanol, water, ammonia water and tetraethyl orthosilicate is 35:8.75:0.5:0.25.
[0055] Furthermore, the mass ratio of the cobalt oxide hollow fiber to tetraethyl orthosilicate is 50-100:0.09-1.
[0056] In some embodiments, the hydrolysis time of the silicon source is 5-7 hours.
[0057] In this process, under alkaline conditions, ethyl orthosilicate is hydrolyzed to coat silica onto the cobalt tetroxide hollow fiber, and finally the reaction generates silica-coated cobalt tetroxide composite hollow fiber.
[0058] The hollow fiber contains Co, S / , and O elements, among which Co and O exist in the form of Co3O4, and S / and O exist in the form of S / O2. The core-shell structure of the two is obvious, and finally a silica-coated cobalt oxide composite hollow fiber material is formed.
[0059] The silica-coated cobalt tetroxide composite hollow fiber material prepared by the present invention has the advantages that, on the one hand, silica is a low-loss material and can optimize the impedance matching of the material, so that electromagnetic waves can smoothly enter the interior of the material without reflection; on the other hand, since cobalt tetroxide is a weak magnetic material, it has a certain magnetic loss for the incident electromagnetic waves; thirdly, the presence of the hollow structure can not only optimize the impedance matching of the material, but also cause multiple scattering of the electromagnetic waves, thereby enhancing the loss of the material to the electromagnetic waves.
[0060] In a third aspect, the present invention provides the application of the composite hollow fiber absorbing material in the direction of electromagnetic wave absorption;
[0061] Furthermore, the composite hollow fiber absorbing material is used in the preparation of electromagnetic wave absorbing devices.
[0062] A composite wave absorbing material is a mixture of the composite hollow fiber wave absorbing material and a binder, wherein the mass ratio of the composite hollow fiber wave absorbing material to the binder is 5-10:2-5.
[0063] The binder and the silica-coated cobalt oxide composite hollow fiber material are mixed by stirring or other means, and the binder is not on the surface of the silica-coated cobalt oxide composite hollow fiber material.
[0064] The composite hollow fiber absorbing material and the binder are mixed evenly in proportion at 30-60°C. After the silica-coated cobalt oxide composite hollow fiber and the binder are evenly mixed, the silica-coated cobalt oxide composite hollow fiber and the binder are basically evenly distributed in the silica-coated cobalt oxide composite hollow fiber composite absorbing material. The role of mixing at a certain high temperature is to enhance the fluidity of the binder and help the binder and the silica-coated cobalt oxide composite hollow fiber to be evenly mixed.
[0065] In a fourth aspect, the present invention provides an electromagnetic wave absorbing device, which is prepared from the composite hollow fiber absorbing material.
[0066] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0067] Example 1
[0068] (1) 1.4 g of polyvinyl pyrrolidone was dissolved in 10 mL of N,N-dimethylformamide solution, and stirred for 30 min to obtain a uniform solution. Then 0.4294 g of cobalt acetylacetonate was added, and stirring was continued at room temperature for 3 h to form a precursor solution.
[0069] (2) The precursor obtained in (1) was transferred into a 15 mL syringe with a steel needle having an inner diameter of 0.6 mm. The syringe was placed in an electrospinning machine, and the positive voltage at the needle was set to 12 kV, the receiving distance was set to 25 cm, and the spinning liquid feed rate was set to 0.3 mL / h. After the spinning was completed, the spinning was placed in an oven at 60°C for 6 h, and the dried precursor fiber was pre-oxidized in an air atmosphere at 180°C for 2 h to ensure the stability of the fiber structure.
[0070] (3) The pre-oxidized fibers are then placed in a muffle furnace and sintered at 500° C. in an air atmosphere for 3 h to remove the polyvinyl pyrrolidone, thereby obtaining cobalt oxide hollow nanofibers.
[0071] (4) Weigh 70 mg of the fiber obtained in step (3), dissolve it in a mixed solution of 35 mL of ethanol, 8.75 mL of water and 0.5 mL of ammonia water, mix well, then add 0.25 mL of tetraethyl orthosilicate, stir continuously at room temperature for 6 h, collect the obtained product by suction filtration, and dry it in an oven at 60° C. for 6 h, finally obtaining a silica-coated cobalt oxide composite hollow fiber.
[0072] Figure 1 This is the XRD pattern of the silicon dioxide-coated cobalt oxide composite hollow fiber prepared in Example 1, confirming that the prepared fiber is silicon dioxide-coated cobalt oxide.
[0073] Figure 2 Figure a is an SEM image of the ferroferric oxide hollow fiber prepared in step (1) of Example 1, in which the average fiber diameter is about 70 nm and the surface is smooth; Figure b is an SEM image of the silica-coated cobalt oxide composite hollow fiber finally obtained in Example 1, in which the average fiber diameter is about 75 nm and the hollow core-shell structure is obvious.
[0074] Figure 3 The TEM image of the fiber obtained in Example 1 shows that the fiber has a hollow structure and a shell thickness of about 14 nm. Figure 3 It can be confirmed that the solid obtained in Example 1 has a hollow structure.
[0075] Example 2
[0076] (1) 1.4 g of polyvinyl pyrrolidone was dissolved in 10 mL of N,N-dimethylformamide solution, and stirred for 30 min to obtain a uniform solution. Then 0.4294 g of cobalt acetylacetonate was added, and stirring was continued at room temperature for 3 h to form a precursor solution.
[0077] (2) The precursor obtained in (1) was transferred into a 15 mL syringe with a steel needle having an inner diameter of 0.6 mm. The syringe was placed in an electrospinning machine, and the positive voltage at the needle was set to 11 kV, the receiving distance was set to 25 cm, and the spinning liquid feed rate was set to 0.3 mL / h. After the spinning was completed, the spinning was placed in an oven at 60°C for 6 h, and the dried precursor fiber was pre-oxidized in an air atmosphere at 180°C for 2 h to ensure the stability of the fiber structure.
[0078] (3) The pre-oxidized fibers are then placed in a muffle furnace and sintered at 500° C. in an air atmosphere for 3 h to remove the polyvinyl pyrrolidone, thereby obtaining cobalt oxide hollow nanofibers.
[0079] (4) Weigh 70 mg of the fiber obtained in (3), dissolve it in a mixed solution of 35 mL of ethanol, 8.75 mL of water and 0.5 mL of ammonia water, mix well, then add 0.25 mL of tetraethyl orthosilicate, stir continuously at room temperature for 6 h, collect the obtained product by suction filtration, and dry it in an oven at 60°C for 6 h, finally obtaining silica-coated cobalt oxide composite hollow fibers.
[0080] Example 3
[0081] (1) 2.4 g of polyvinyl pyrrolidone was dissolved in 10 mL of N,N-dimethylformamide solution, and stirred for 30 min to obtain a uniform solution. Then 1.1324 g of cobalt acetylacetonate was added, and stirring was continued at room temperature for 2.5 h to form a precursor solution.
[0082] (2) The precursor obtained in (1) was transferred into a 15 mL syringe with a steel needle having an inner diameter of 0.6 mm. The syringe was placed in an electrospinning machine, and the positive voltage at the needle was set to 14 kV, the receiving distance was set to 25 cm, and the spinning liquid feed rate was set to 0.3 mL / h. After the spinning was completed, the spinning was placed in an oven at 60°C for 6 h, and the dried precursor fiber was pre-oxidized in an air atmosphere at 180°C for 2 h to ensure the stability of the fiber structure.
[0083] (3) The pre-oxidized fibers are then placed in a muffle furnace and sintered at 700° C. in an air atmosphere for 3 h to remove the polyvinyl pyrrolidone, thereby obtaining cobalt oxide hollow nanofibers.
[0084] (4) Weigh 70 mg of the fiber obtained in (3), dissolve it in a mixed solution of 35 mL of ethanol, 8.75 mL of water and 0.5 mL of ammonia water, mix well, then add 0.25 mL of tetraethyl orthosilicate, stir continuously at room temperature for 6 h, collect the obtained product by suction filtration, and dry it in an oven at 60°C for 6 h, finally obtaining silica-coated cobalt oxide composite hollow fibers.
[0085] Performance Testing
[0086] The silica-coated cobalt tetroxide composite hollow fiber prepared in Example 1 and paraffin were mixed in a mass ratio of 7:3 to obtain a silica-coated cobalt tetroxide composite hollow fiber composite absorbing material. The electromagnetic parameters were tested using an Ag / lent Technolog / esE8363A electromagnetic wave vector network analyzer, and the absorbing performance of the material was calculated based on the electromagnetic parameters to obtain the following: Figure 6 Results shown.
[0087] Figure 4It can be seen that the silicon dioxide-coated cobalt tetroxide composite hollow fiber composite absorbing material prepared in Example 1 has strong dielectric loss.
[0088] Figure 5 It can be seen that the silicon dioxide-coated cobalt tetroxide composite hollow fiber composite absorbing material prepared in Example 1 has a certain magnetic loss.
[0089] from Figure 6 It can be seen that the silicon dioxide-coated cobalt tetroxide composite hollow fiber absorbing material prepared in Example 1 has excellent electromagnetic wave absorption performance. The reflection loss of electromagnetic waves at a frequency of 7.65 GHz reaches -29.1 dB, and the matching thickness is only 4.27 mm.
[0090] Depend on Figure 7 As shown, the silica-coated cobalt oxide composite hollow fiber absorbing material prepared in Example 2 has excellent electromagnetic wave absorption performance, and the reflection loss of electromagnetic waves at a frequency of 7.3 GHz reaches -30.8 dB, and the matching thickness is only 4.20 mm.
[0091] Comparative Example 1
[0092] The difference from Example 1 is that the mass ratio of the silicon dioxide-coated cobalt oxide composite hollow fiber to paraffin is 1: 1. The electromagnetic parameter test was performed using an Ag / lent Technolog / es E8363A electromagnetic wave vector network analyzer, and the wave absorption performance of the material was calculated based on the electromagnetic parameters.
[0093] Figure 8 The performance diagram of the sample prepared in comparative example 1 shows that within the range of 2-18 GHz, the reflection loss of electromagnetic waves at a frequency of 9.6 GHz reaches -5.4 dB, and the matching thickness is 4.45 mm. The reflection loss is far less than that of example 1, and the wave absorbing performance is poor.
[0094] Comparative Example 2
[0095] The difference from Example 1 is that step (4) is removed, and the rest remain unchanged. Electromagnetic parameter testing is performed using an Ag / lentTechnolog / es E8363A electromagnetic wave vector network analyzer, and the wave absorption performance of the material is calculated based on the electromagnetic parameters.
[0096] Fig. 9 This is the performance diagram of the sample prepared in comparative example 2. It can be seen that within the range of 2-18 GHz, the reflection loss of electromagnetic waves at a frequency of 6.2 GHz reaches -19.4 dB, and the matching thickness is 5.00 mm. The reflection loss is not as good as that of example 1, and the wave absorbing performance is poor.
[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite hollow fiber absorbing material, Features: The composite hollow fiber absorbing material comprises a cobalt oxide hollow fiber and a silicon dioxide coating layer coated on the outside thereof; The outer diameter of the cobalt tetroxide hollow fiber is 60-90 nm, and the inner diameter is 20-40 nm; The thickness of the silicon dioxide coating layer is 10-20 nm; The preparation method of the composite hollow fiber absorbing material comprises the following steps: Electrospinning a precursor solution of cobalt salt to obtain fibers; calcining the fiber to obtain cobalt tetroxide hollow fiber; The cobalt tetroxide hollow fiber is dispersed in a silicon source solution, and the silicon source is hydrolyzed to obtain silicon dioxide, thereby obtaining a silicon dioxide-coated cobalt tetroxide composite hollow fiber absorbing material; The silicon source solution is a mixed solution of ethanol, water, ammonia water and tetraethyl orthosilicate; The mass ratio of cobalt oxide hollow fiber to tetraethyl orthosilicate is 50-100:0.09-1; The composite wave absorbing material is obtained by compounding the silicon dioxide-coated cobalt tetroxide composite hollow fiber wave absorbing material and a binder, wherein the mass ratio of the silicon dioxide-coated cobalt tetroxide composite hollow fiber wave absorbing material to the binder is 5-10:2-5; The calcination atmosphere was air.
2. The method for preparing the composite hollow fiber absorbing material according to claim 1, Features: The precursor solution of the cobalt salt is a mixed solution of the cobalt salt and a surfactant; Furthermore, the cobalt salt is cobalt acetylacetonate or cobalt nitrate hexahydrate; Furthermore, the surfactant is polyvinyl pyrrolidone or polyacrylonitrile; Further, the solvent of the precursor solution of the cobalt salt is N,N-dimethylformamide; Furthermore, the concentration of the cobalt salt is 0.005-0.2 g / mL, and the concentration of the surfactant is 0.05-0.4 g / mL.
3. The method for preparing the composite hollow fiber absorbing material according to claim 2, Features: The concentration of the cobalt salt is 0.06-0.12 g / mL, and the concentration of the surfactant is 0.05-0.1 g / mL.
4. The method for preparing the composite hollow fiber absorbing material according to claim 1, Features: The temperature of electrospinning is 20-40 ℃ and the voltage is 10-15V.
5. The method for preparing the composite hollow fiber absorbing material according to claim 1, Features: The temperature of electrospinning is 30-40 °C and the voltage is 10-12V.
6. The method for preparing the composite hollow fiber absorbing material according to claim 1, Features: The temperature of electrospinning was 40 °C and the voltage was 12 V.
7. The method for preparing the composite hollow fiber absorbing material according to claim 1, Features: The calcination temperature is 400-800 °C, the heating rate is 1-5 °C / min, and the reaction time is 0.5-8 h; In the silicon source solution, the volume ratio of ethanol, water, ammonia water and tetraethyl orthosilicate is 30-50:5-15:0.2-1:0.1-1.
8. The method for preparing the composite hollow fiber absorbing material according to claim 1, Features: The calcination temperature is 400-600 ℃, the heating rate is 1-3 ℃ / min, and the reaction time is 1-4 h.
9. The method for preparing the composite hollow fiber absorbing material according to claim 7, Features: In the silicon source solution, the volume ratio of ethanol, water, ammonia water and tetraethyl orthosilicate is 30-40:5-10:0.3-0.8:0.1-0.
5.
10. The method for preparing the composite hollow fiber absorbing material according to claim 7, Features: In the silicon source solution, the volume ratio of ethanol, water, ammonia water and tetraethyl orthosilicate is 35:8.75:0.5:0.
25.
11. The method for preparing the composite hollow fiber absorbing material according to claim 1, Features: The hydrolysis time of the silicon source is 5-7h.
12. Application of the composite hollow fiber absorbing material prepared by the method according to claim 1 in the absorption of electromagnetic waves.
13. Use of the composite hollow fiber absorbing material prepared according to the method of claim 1 in preparing electromagnetic wave absorbing devices.
14. An electromagnetic wave absorbing device, Features: The composite hollow fiber absorbing material is prepared by the method described in claim 1.
Citation Information
Patent Citations
Ferroferric oxide hollow nanofiber preparation method
CN106498561A
Preparation method of ferroferric oxide / silicon dioxide composite fiber wave-absorbing material
CN110042500A
Carbon nanotube-based three-dimensional network structure composite wave-absorbing material and preparation method thereof
CN111916916A
Hollow metal fiber for absorbing electromagnetic wave and its manufacturing method
JP2009185378A
Method for manufacturing magnetic fiber using catechol polymer
KR101489727B1
